High-activity erosion-resistant oxygen electrode as well as preparation method and application thereof

By using a core-shell structure in the oxygen electrode, the conductive oxide electrode grains are coated with doped cerium oxide nanoparticles, the problem of oxygen electrode erosion in solid oxide batteries under operating conditions is solved, and high activity and corrosion resistance are achieved , ensure long-term stable operation and high performance of the battery under medium and low temperature conditions.

CN119297298AActive Publication Date: 2025-01-10ZHUHAI INST OF ADVANCED TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411348424.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Under operating conditions, the oxygen electrodes of existing solid oxide batteries are easily eroded by carbon dioxide and moisture in the air, resulting in a decline in battery performance. In addition, traditional oxygen electrode materials have low conductivity and catalytic activity under medium and low temperature conditions, making it difficult to operate stably for a long time. .

Method used

The oxygen electrode with core-shell structure is adopted, with conductive oxide electrode grains as the main body, and doped cerium oxide nanoparticles as the coated phase. The mass percentage of doped cerium oxide nanoparticles is 0.5-8% to improve the chemical stability of the oxygen electrode. and catalytic activity, inhibiting the erosion of water vapor, carbon dioxide and chromium oxide.

Benefits of technology

It achieves high activity and corrosion resistance of oxygen electrodes, ensures long-term and stable operation of solid oxide batteries under operating conditions, and improves battery performance and tolerance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005061633590000011
    Figure HDA0005061633590000011
  • Figure HDA0005061633590000012
    Figure HDA0005061633590000012
  • Figure HDA0005061633590000013
    Figure HDA0005061633590000013
Patent Text Reader

Abstract

The invention belongs to the technical field of solid oxide batteries, and provides a high-activity erosion-resistant oxygen electrode and a preparation method and application thereof. According to the oxygen electrode provided by the invention, the doped cerium oxide nanoparticles are used as the shell, the conductive oxide electrode crystal grains are used as the core, the mass percentage of the doped cerium oxide nanoparticles in the oxygen electrode is 0.5-8%, and the doped cerium oxide nanoparticles are used for coating the conductive oxide main body material, so that the high activity of the oxygen electrode is ensured, and the conductivity of the conductive oxide main body material is improved. The oxygen electrode has the characteristic of stable chemical properties, can effectively inhibit erosion of water vapor, carbon dioxide and chromic oxide to the oxygen electrode, has excellent tolerance, and is further used for preparing a solid oxide battery, so that the long-term stable operation of the battery under working conditions is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid oxide batteries, and more specifically, to a highly active and corrosion-resistant oxygen electrode and a preparation method and application thereof. Background Art

[0002] Solid oxide cells are an advanced energy conversion device. In fuel cell mode, solid oxide cells directly convert the chemical energy in fuel gases such as hydrogen, carbon monoxide and methane into electrical energy to generate electricity. In electrolysis mode, solid oxide cells can use unstable electricity generated by wind and solar renewable energy, or excess electricity when the power grid is idle, to electrolyze water to produce hydrogen or electrolyze carbon dioxide to produce carbon monoxide to achieve energy storage. The main components of solid oxide cells include oxygen electrodes, fuel electrodes and electrolytes. Among them, the processes of fuel gas oxidation, water reduction to hydrogen and carbon dioxide reduction to carbon monoxide are carried out at the fuel electrode, while the oxygen electrode is usually exposed to the air atmosphere and consumes or generates oxygen according to the battery operation mode.

[0003] Under the actual application conditions of solid oxide batteries, carbon dioxide and moisture in the air can easily corrode the oxygen electrode, causing battery performance to decline and affecting battery stability. In addition, in order to increase power, a connector is required to connect multiple single cells in series into a battery stack. Solid oxide battery connectors are usually made of iron-chromium alloy or nickel-chromium alloy, such as Fe-10Cr, SUS 430, AL 453, Inconel 600 and ASL 528. Under operating conditions (700-900°C), at the oxygen electrode end, the chromium in the iron-chromium alloy connector will be oxidized into gaseous chromium oxide (CrO3) and diffuse into the electrode atmosphere. Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O3, Ba 0.9 Co 0.7 Fe 0.2 Nb 0.1 O3 and SrCo 0.7 Fe 0.2 Nb 0.1 Perovskite oxides with alkaline earth metals as A-site metal ions, such as LaO3, have excellent electrochemical properties and catalytic activity, enabling the battery to perform well at low temperatures below 650°C. However, under working conditions, alkaline earth metal ions easily react with impurities such as water, carbon dioxide, and chromium oxide in the working atmosphere, resulting in poisoning and failure, causing battery performance degradation. 0.6 Sr 0.4 FeO3、La 0.8 Sr 0.2 MnO3 and LaNi 0.6 Fe 0.4Traditional oxygen electrode materials represented by O3 often show good stability, but their ion-electron mixed conductivity and catalytic activity are relatively low, making them difficult to use in medium- and low-temperature solid oxide batteries operating at 500-800°C. Cerium oxide doped with heterovalent metal ions, such as gadolinium oxide doped cerium oxide, samarium oxide doped cerium oxide, and lanthanum oxide doped cerium oxide, show good oxygen ion conductivity and chemical stability. However, in an oxygen atmosphere, the catalytic activity of cerium oxide in oxygen exchange reactions is low, and it cannot be directly used as an oxygen electrode material. As can be seen from the above, solid oxide batteries composed of the above materials are currently difficult to operate stably and for a long time under working conditions.

[0004] Therefore, there is an urgent need to develop an oxygen electrode with good stability, high conductivity and catalytic activity, and corrosion resistance, which can be further used to produce solid oxide batteries that maintain high performance and long-term stable operation under working conditions. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a highly active and corrosion-resistant oxygen electrode and a preparation method and application thereof. The oxygen electrode provided by the present invention has good stability, high conductivity and catalytic activity, and corrosion resistance, and is further used to prepare a solid oxide battery, which can maintain high performance under working conditions and operate stably for a long time.

[0006] A first aspect of the present invention provides a highly active, corrosion-resistant oxygen electrode.

[0007] Specifically, a highly active and corrosion-resistant oxygen electrode is provided, wherein the oxygen electrode is a core-shell structure, wherein the core is a conductive oxide electrode grain, and the shell is doped cerium oxide nanoparticles, and the mass percentage of the doped cerium oxide nanoparticles in the oxygen electrode is 0.5-8%.

[0008] The composite, core-shell structured oxygen electrode provided by the present invention uses doped cerium oxide nanoparticles as the coating phase (shell) and conductive oxide electrode grains as the main phase (core), wherein the conductive oxide electrode grains are coated with doped cerium oxide nanoparticles, which can give the oxygen electrode the advantage of high chemical stability while ensuring the high activity of the oxygen electrode, and can also effectively inhibit the corrosion of water vapor, carbon dioxide and chromium oxide on the oxygen electrode, so that the oxygen electrode exhibits excellent tolerance. Further, the oxygen electrode is used to prepare a solid oxide battery, which is beneficial to ensure the long-term stable operation of the battery under working conditions. In summary, the present invention combines the advantages of doped cerium oxide nanoparticles with high chemical stability and highly active conductive oxides, while effectively avoiding the disadvantages of each material, and exhibits high activity and tolerance to air impurities.

[0009] Preferably, the mass percentage of the cerium oxide nanoparticles doped in the oxygen electrode is 1-5%.

[0010] Preferably, the particle size of the conductive oxide electrode crystal particles is 200-400 nm. Electrode crystal particles with a small particle size are conducive to the atomization and coating of the slurry.

[0011] Preferably, the conductive oxide electrode grains are perovskite-type conductive oxides.

[0012] Further preferably, the conductive oxide electrode grains are Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O3, Ba 0.9 Co 0.7 Fe 0.2 Nb 0.1 O3 (BCFN for short), La 0.6 Sr 0.4 At least one of CoO3. These materials are highly active and exhibit excellent ionic conductivity, electronic conductivity and catalytic activity in air or oxygen atmosphere.

[0013] Preferably, the doped cerium oxide nanoparticles (shells) are cerium oxide nanoparticles doped with rare metal oxides. The cerium oxide nanoparticles doped with rare metal oxides are obtained by doping cerium oxide nanoparticles with rare metal oxides.

[0014] Further preferably, the doped cerium oxide nanoparticles (shells) are at least one of gadolinium oxide-doped cerium oxide nanoparticles, samarium oxide-doped cerium oxide nanoparticles, and lanthanum oxide-doped cerium oxide nanoparticles.

[0015] More preferably, the doped cerium oxide nanoparticles (shells) are gadolinium oxide doped cerium oxide nanoparticles (Ce 0.8 G 0.2 O 1.9 , referred to as GDC).

[0016] Preferably, the molar amount of the rare metal element in the doped cerium oxide nanoparticles accounts for 5-25% of the total molar amount of the metal elements, and the total molar amount of the metal elements is the sum of the molar amounts of all the metal elements in the doped cerium oxide nanoparticles.

[0017] A second aspect of the present invention provides a method for preparing a highly active and corrosion-resistant oxygen electrode.

[0018] A method for preparing a highly active and corrosion-resistant oxygen electrode comprises the following steps:

[0019] The conductive oxide electrode grains (core) and the precursor solution of doped cerium oxide nanoparticles (shell) are mixed to obtain a mixed slurry, which is then dried to obtain a precursor-coated powder, followed by a first calcination to obtain a composite electrode powder, and then the composite electrode powder is mixed with battery glue to obtain an electrode slurry, which is then subjected to a second calcination to obtain the oxygen electrode.

[0020] The preparation method of the oxygen electrode provided by the invention is efficient, low in cost and has wide applicability.

[0021] Preferably, the mass volume concentration of the solute in the doped cerium oxide nanoparticle precursor solution is 10-60 mg / mL.

[0022] Preferably, the raw materials for preparing the doped cerium oxide nanoparticles include: cerium salt (such as Ce(NO3)4) and doping metal salt.

[0023] Preferably, the doping metal salt is at least one of Gd(NO3)3, La2(CO3)3, BaCO3, SrCO3, Co2O3, Fe2O3, and Nb2O5.

[0024] Preferably, the method for preparing the doped cerium oxide nanoparticle precursor solution comprises the following steps: mixing the preparation raw materials for the doped cerium oxide nanoparticles, dissolving them in water to obtain a precursor salt-water precursor solution, and then dissolving them in ethanol to obtain a salt-water-ethanol precursor solution, that is, obtaining the doped cerium oxide nanoparticle precursor solution.

[0025] Preferably, the volume ratio of the precursor salt-water precursor solution to ethanol is 1:(20-80).

[0026] Preferably, the conductive oxide electrode grains and the raw materials for preparing the doped cerium oxide nanoparticles are mixed and then ball-milled to obtain a mixed slurry.

[0027] Further preferably, the conductive oxide electrode grains (cores) and the doped cerium oxide nanoparticle precursor solution are mixed, placed in a ball mill, and ball milling beads of the same mass as the conductive oxide electrode grains are added, and ball milling is performed at a rotation speed of 300-600 rpm for 12-36 hours to obtain a mixed slurry.

[0028] Preferably, the raw materials for preparing the battery glue include: ethyl cellulose and rosin alcohol.

[0029] Preferably, the preparation method of the battery glue comprises: dissolving ethyl cellulose in rosin alcohol to obtain the battery glue.

[0030] Further preferably, the preparation method of the battery glue comprises: dissolving ethyl cellulose in rosin alcohol under the condition of heating at 50-80° C. in a water bath, wherein the mass fraction of ethyl cellulose in the battery glue is 5-20%, and stirring at a speed of 300-600 rpm, and standing to cool to 20-30° C. after complete dissolution.

[0031] Preferably, the drying is spray drying, wherein the mixed slurry is atomized in hot air and the solvent (water and ethanol) is removed to obtain a precursor-coated powder.

[0032] Preferably, the spray gun pressure of the spray drying is 1.5-4 bar, and / or the hot air temperature of the spray drying is 30-100°C.

[0033] Further preferably, the spray gun pressure of the spray drying is 2-4 bar, and / or the hot air temperature of the spray drying is 70-90°C.

[0034] Preferably, after the electrode slurry is prepared, the electrode slurry is then screen-printed onto a solid oxide electrolyte substrate, followed by a second calcination to prepare the oxygen electrode.

[0035] Preferably, the temperature of the first calcination is 500-700° C., and / or the time of the first calcination is 0.5-2 h.

[0036] Further preferably, the temperature of the first calcination is 600-650° C., and / or the time of the first calcination is 1-1.5 h.

[0037] Preferably, the temperature of the second calcination is 850-1200° C., and / or the time of the second calcination is 1-4 h.

[0038] More preferably, the temperature of the second calcination is 850-1150° C., and / or the time of the second calcination is 2-2.5 h.

[0039] During the first calcination process, the precursor reacts to form conductive oxide electrode grains, while encapsulating the doped cerium oxide nanoparticles in the form of nanoparticles.

[0040] Preferably, the block obtained after the calcination is crushed to obtain a powder, ball-milled at least twice, and then dried and calcined repeatedly to obtain the oxygen electrode.

[0041] A third aspect of the present invention provides an application of a highly active, corrosion-resistant oxygen electrode.

[0042] The invention discloses an application of a highly active and corrosion-resistant oxygen electrode in preparing a battery.

[0043] Preferably, the battery is a solid oxide battery.

[0044] A fourth aspect of the present invention provides a solid oxide battery.

[0045] A solid oxide battery comprises the highly active and corrosion-resistant oxygen electrode, a fuel electrode and an electrolyte.

[0046] Preferably, the electrolyte is at least one of lanthanum strontium gallium magnesium (LSGM), yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), samarium oxide-doped cerium oxide (SDC), barium zirconium yttrium (BZY), and barium cerium zirconium yttrium ytterbium (BZCYYb).

[0047] Preferably, the fuel electrode is at least one of nickel oxide mixed with YSZ (Ni-YSZ), nickel oxide mixed with GDC (Ni-GDC), and lanthanum strontium chromium iron (LSCrF).

[0048] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0049] The oxygen electrode provided by the present invention uses doped cerium oxide nanoparticles as a shell and conductive oxide electrode grains as a core, wherein the mass percentage of doped cerium oxide nanoparticles in the oxygen electrode is 0.5-8%. The doped cerium oxide nanoparticles are used to coat the main material of the conductive oxide electrode grains, which can not only ensure the high activity of the oxygen electrode, but also give the oxygen electrode the characteristics of stable chemical properties, and can effectively inhibit the corrosion of water vapor, carbon dioxide and chromium oxide to the oxygen electrode, so that the oxygen electrode exhibits excellent tolerance. Further, the oxygen electrode of the present invention is used to prepare a solid oxide battery, which is conducive to ensuring the high performance and long-term stable operation of the battery under working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 It is a scanning electron microscope (SEM) comparison diagram of the BCFN oxygen electrode prepared in Comparative Example 1 and the GDC@BCFN oxygen electrode prepared in Example 1;

[0051] Figure 2 Schematic diagram of the operation process of the oxygen electrode of Example 1;

[0052] Figure 3 Schematic diagram of the operation process of the oxygen electrode of Comparative Example 1;

[0053] Figure 4 This is a polarization impedance diagram of the 5% GDC@BCFN oxygen electrode of Example 1 running at 650°C in air with a water content of 3% and a carbon dioxide content of 5% for 20 hours;

[0054] Figure 5This is a graph showing the change in polarization impedance of the oxygen electrode of Comparative Example 1 when it is operated in air at 650° C., with a water content of 3% and a carbon dioxide content of 5% for 20 hours;

[0055] Figure 6 This is a SEM comparison of the BCFN oxygen electrode prepared in Comparative Example 1 and the GDC@BCFN oxygen electrode prepared in Example 1 after operation in air with a water content of 3% and a carbon dioxide content of 5%;

[0056] Figure 7 This is the polarization impedance diagram of the oxygen electrode of Example 1 operating at 800°C with chromium-iron alloy as the connector;

[0057] Figure 8 is the polarization impedance diagram of the oxygen electrode of comparative example 1 operated at 800°C with chromium-iron alloy as the connector;

[0058] Fig. 9 The stability diagram of the oxygen electrodes of Examples 1-3 and Comparative Example 1 at 800° C. with chromium-iron alloy as the connector;

[0059] Fig.10 1 is the polarization impedance diagram of oxygen electrodes of Example 1, Comparative Example 1 and Comparative Example 2;

[0060] Fig.11 Graph showing the performance test results of the oxygen electrodes of Comparative Example 1, Example 2, Example 3, Example 1 and Comparative Example 3 in an air atmosphere at 800°C. DETAILED DESCRIPTION

[0061] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0062] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0063] The preparation method of BCFN used in the present invention comprises the following steps:

[0064] The precursor powder and the solvent are mixed, and ball milling beads of the same mass as the precursor powder are added for ball milling at a rotation speed of 400 r / min and a ball milling time of 24 hours to obtain a mixed slurry. The mixed slurry is dried at 80°C for 24 hours to obtain a mixed powder. The mixed slurry is calcined at 1100°C for 12 hours and crushed to obtain a powder. The above steps are then repeated to obtain BCFN.

[0065] The precursor powder includes BaCO3, Co2O3, Fe2O3, and Nb2O5 with a molar ratio of 9:3.5:1:0.5.

[0066] Example 1

[0067] A highly active and corrosion-resistant oxygen electrode (abbreviated as GDC@BCFN or 5%GDC@BCFN) has a core-shell structure; the core is electron-ion mixed conductor oxide electrode grains BCFN with a particle size of about 300nm; the shell is gadolinium oxide doped cerium oxide nanoparticles GDC, wherein the molar amount of gadolinium (Gd) accounts for 20% of the total molar amount of metal elements in GDC; in the oxygen electrode, the mass percentage of GDC is 5wt%.

[0068] A method for preparing 5% GDC@BCFN comprises the following steps:

[0069] (1) According to the chemical mass ratio of Ce and Gd in GDC, Ce(NO3)4 and Gd(NO3)3 were weighed and mixed, and completely dissolved in deionized water to prepare a 30 mg / mL nitrate aqueous solution;

[0070] (2) adding anhydrous ethanol to a nitrate aqueous solution and mixing them completely, wherein the volume ratio of the nitrate aqueous solution to the anhydrous ethanol is 1:50, to prepare a nitrate-water-ethanol precursor solution;

[0071] (3) Calculate the mass of BCFN based on 5% GDC@BCFN and weigh it, pour it into the nitrate-water-ethanol precursor solution, add ball milling beads of the same mass as BCFN, and ball mill at a speed of 450 rpm for 24 h to obtain a precursor-BCFN mixed slurry;

[0072] (4) Using a spray dryer, the mixed slurry is sprayed out at a pressure of 2 bar, and the mixed slurry is atomized in hot air at 80°C. After the ethanol and water are volatilized, a powder coated with a nitrate precursor is obtained. Subsequently, the coated powder is collected and first calcined at 600°C for 1 hour. The precursor reacts to generate GDC, thereby obtaining a 5% GDC@BCFN electrode powder.

[0073] (5) mixing ethyl cellulose and pinene alcohol, and heating and stirring to completely dissolve the ethyl cellulose in the pinene alcohol to prepare a battery glue; wherein the mass percentage of the ethyl cellulose in the battery glue is 6wt%;

[0074] (6) 5% GDC@BCFN electrode powder was evenly mixed with electrode glue to prepare electrode slurry, which was screen-printed onto LSGM solid oxide electrolyte and then subjected to a second calcination at 1000 °C for 2 h to obtain 5% GDC@BCFN oxygen electrode.

[0075] Example 2

[0076] A highly active and corrosion-resistant oxygen electrode (referred to as 1% GDC@BCFN) is different from Example 1 in that the mass percentage of GDC in the oxygen electrode is replaced with 1wt%.

[0077] Example 3

[0078] A highly active and corrosion-resistant oxygen electrode (referred to as 3% GDC@BCFN) is different from Example 1 in that the mass percentage of GDC in the oxygen electrode is replaced with 3wt%.

[0079] Comparative Example 1 (BCFN alone)

[0080] An oxygen electrode, which is different from Example 1 in that it uses BCFN alone (without GDC), and the mass of the oxygen electrode of Comparative Example 1 is equal to the mass of the 5% GDC@BCFN oxygen electrode finally prepared in Example 1.

[0081] Comparative Example 2 (Preparation method of direct mixing)

[0082] An oxygen electrode (BCFN-5% GDC for short) is different from Example 1 in that the preparation method is changed to: directly mixing GDC powder and BCFN powder evenly to obtain BCFN-5% GDC electrode grains. The remaining steps are the same as Example 1.

[0083] Comparative Example 3 (Increasing the proportion of GDC)

[0084] A highly active and corrosion-resistant oxygen electrode (referred to as 10% GDC@BCFN) is different from Example 1 in that the mass percentage of GDC in the oxygen electrode is replaced by 10%.

[0085] Product effect testing

[0086] 1. Microscopic morphology

[0087] The microscopic morphologies of the BCFN oxygen electrode of Comparative Example 1 and the GDC@BCFN oxygen electrode prepared in Example 1 are as follows: Figure 1 A. Figure 1 As shown in B, by comparison, it can be seen that the oxygen electrode of Example 1 contains GDC nanoparticles and is coated on the surface of BCFN grains.

[0088] 2. Electrochemical performance test of oxygen electrode (test of oxygen electrode's tolerance to water and carbon dioxide)

[0089] like Figure 2 As shown, the coated high-activity and corrosion-resistant oxygen electrode is prepared in Example 1, and the surface of the conductive oxide electrode grains (core) is coated with doped cerium oxide nanoparticles (shell), which can effectively inhibit the corrosion of CO2, H2O and CrO3 to the oxygen electrode under working conditions, while maintaining the high activity of the conductive oxide electrode grains (core).

[0090] like Figure 3 As shown, the BCFN oxygen electrode of Comparative Example 1 is a traditional solid oxide oxygen electrode, the surface of which is not coated with doped cerium oxide nanoparticles (shell), and it is difficult to inhibit the corrosion of CO2, H2O and CrO3 on the oxygen electrode.

[0091] The electrochemical performance of the oxygen electrode can be indicated by its polarization impedance. The larger the polarization impedance, the slower the oxygen exchange reaction rate in the oxygen electrode and the worse the electrode performance. The tolerance test of the oxygen electrodes of Example 1 and Comparative Example 1 was carried out, and the polarization impedance was as follows:

[0092] like Figure 4 As shown in FIG. 1 , the 5% GDC@BCFN oxygen electrode of Example 1 was operated in air at 650°C, with a water content of 3% and a carbon dioxide content of 5% for 20 hours, and the polarization impedance did not change significantly. Figure 5 As shown in the figure, the uncoated BCFN oxygen electrode has a significant increase in polarization impedance and poor electrode performance during operation at 650°C, 3% water content and 5% carbon dioxide content in air for 20 hours. Figure 4 and Figure 5 Beginning is the starting operation, 1hour is the operation after 1 hour, 20hours is the operation after 20 hours, Z' is the real part of impedance, -Z" is the imaginary part of impedance.

[0093] The performance test results of the oxygen electrodes of Example 1 and Comparative Example 1 are summarized in Table 1.

[0094] Table 1 Polarization impedance of oxygen electrodes in Example 1 and Comparative Example 1 at different operating times in air at 650°C, 3% water content and 5% carbon dioxide content (unit: ohm*cm 2 )change

[0095] Starting 1h 20h Example 1 0.08 0.11 0.15 Comparative Example 1 0.08 0.25 0.69

[0096] It can be seen from Table 1 that under the same conditions, after running for 20 hours, the polarization impedance of Comparative Example 1 increased to 0.69 ohm*cm 2 , while Example 1 only slightly increased to 0.15 ohm*cm 2 , and still maintained at around the initial polarization impedance, indicating that the oxygen electrode of Example 1, after being coated with 5% GDC nanoparticles, is conducive to maintaining the activity of the alkaline earth metal-based electrode, while significantly improving the tolerance of the oxygen electrode to water and carbon dioxide.

[0097] Example 1, Comparative Example 1 The microscopic morphology of the oxygen electrode after operation in air with a water content of 3% and a carbon dioxide content of 5% are as follows: Figure 6 A. Figure 6As shown in B, by comparison, it can be seen that under the same operating conditions, H2O and CO2 in the air corrode the oxygen electrode of Comparative Example 1 by reacting with BCFN, while the GDC nanoparticles in the oxygen electrode of Example 1 can effectively inhibit the corrosion process, and the morphology of the oxygen battery before and after operation changes little.

[0098] 3. Stability test of oxygen electrode (chrome corrosion resistance test)

[0099] The oxygen electrodes of Example 1 and Comparative Example 1 were respectively operated at 800°C with chromium-iron alloy as the connector, and the changes in polarization impedance during the operation for 96 hours were recorded. Figure 7 As shown, the polarization impedance of 5% GDC@BCFN in Example 1 did not change significantly during operation, indicating that its electrochemical properties were stable. Figure 8 As shown, the polarization impedance of BCFN increases significantly during the operation of Comparative Example 1, indicating that its electrochemical stability is poor. The chromium corrosion resistance of the oxygen electrode of Example 1 and Comparative Example 1 is compared, and the results are summarized in Table 2.

[0100] Table 2 Polarization impedance of oxygen electrode of Example 1 and Comparative Example 1 at 800°C, 5% GDC@BCFN and BCFN, oxygen electrode with chromium-iron alloy as connector (unit: ohm*cm 2 ) Changes

[0101] start 48h 96h Example 1 0.015 0.019 0.023 Comparative Example 1 0.022 0.041 0.065

[0102] It can be seen from Table 2 that after 96 hours of operation, the polarization impedance of the oxygen electrode of Example 1 increased from 0.015 to 0.023 ohm*cm 2 , the increase rate is 8.54×10 -5 ohm*cm 2 / h; while the polarization impedance of the oxygen electrode of Comparative Example 1 increased from 0.022 to 0.065 ohm*cm 2 , the increase rate is 4.48×10 -4 ohm*cm 2 / h. The above results show that Example 1, in which 5% GDC nanoparticles are coated on BCFN, can effectively reduce the rate of increase of polarization impedance by one order of magnitude, indicating that the 5% GDC@BCFN oxygen electrode not only exhibits high performance but also has excellent resistance to chromium corrosion.

[0103] Comparison of the operation of oxygen electrodes with different GDC coating amounts at 800°C with chromium-iron alloy as the connector shows that Fig. 9 As shown, the results show that GDC in nanoparticle form can maintain the high performance of alkaline earth metal-based electrodes, and the addition of a very small amount (1%) of GDC can significantly improve the corrosion resistance of the electrode. As the GDC content increases, the GDC@BCFN becomes more stable. Fig. 9 Where Time is the running time and Resistance is the resistance.

[0104] 4. Comparison of the performance of oxygen electrodes (BCFN, 5% GDC@BCFN, BCFN-5% GDC) of Comparative Example 1, Example 1 and Comparative Example 2

[0105] At 800℃, in air atmosphere, the performance test results of three oxygen electrodes, BCFN, 5%GDC@BCFN and BCFN-5%GDC obtained by different preparation methods are shown in the figure. Fig.10 As shown, the polarization impedances of the three are 0.022, 0.0156 and 0.046 ohm*cm respectively. 2 From the results, it can be seen that compared with Comparative Example 1, Comparative Example 2 uses a traditional mechanical mixing method to prepare a BCFN-5% GDC composite electrode, and the addition of GDC actually reduces the electrode performance; while the GDC@BCFN prepared by the method of Example 1 can improve the excellent performance of the electrode material.

[0106] 5. Comparative Example 1, Example 2, Example 3, Performance Comparison of Oxygen Electrodes of Example 1 and Comparative Example 3 (BCFN, 1% GDC@BCFN, 3% GDC@BCFN, 5% GDC@BCFN, 10% GDC@BCFN)

[0107] At 800℃, in air atmosphere, the performance test results of five oxygen electrodes, BCFN, and 1% GDC@BCFN, 3% GDC@BCFN, 5% GDC@BCFN, and 10% GDC@BCFN prepared by the same method but with different coating amounts, are shown in the figure. Fig.11 As shown, the polarization impedances of the above five oxygen electrodes are 0.022, 0.021, 0.015, 0.0156 and 0.045 ohm*cm respectively. 2 The results show that, compared with Comparative Example 1, 1%, 3%, and 5% GDC nanoparticles coated BCFN grains prepared in Examples 1-3 can improve the performance of the oxygen electrode, but the excessive amount of GDC (10%) in Comparative Example 3 will increase the polarization impedance and cause the electrode performance to deteriorate.

Claims

1. An oxygen electrode, characterized in that The oxygen electrode is a core-shell structure, the core is a conductive oxide electrode crystal grain, the shell is doped cerium oxide nanoparticles, and the mass percentage of the doped cerium oxide nanoparticles in the oxygen electrode is 0.5-8%.

2. The oxygen electrode according to claim 1, characterized in that The mass percentage of the cerium oxide nanoparticles doped in the oxygen electrode is 1-5%.

3. The oxygen electrode according to claim 1, characterized in that The particle size of the conductive oxide electrode grains is 200-400 nm.

4. The oxygen electrode according to claim 1, characterized in that The conductive oxide electrode grains are perovskite-type conductive oxides.

5. The oxygen electrode according to claim 1, characterized in that The doped cerium oxide nanoparticles are cerium oxide nanoparticles doped with rare metal oxides.

6. The oxygen electrode according to claim 5, characterized in that The doped cerium oxide nanoparticles are at least one of gadolinium oxide-doped cerium oxide nanoparticles, samarium oxide-doped cerium oxide nanoparticles, and lanthanum oxide-doped cerium oxide nanoparticles.

7. The oxygen electrode according to claim 5 or 6, characterized in that The molar amount of the rare metal element in the doped cerium oxide nanoparticles accounts for 5-25% of the total molar amount of the metal elements, and the total molar amount of the metal elements is the sum of the molar amounts of all the metal elements in the doped cerium oxide nanoparticles.

8. A method for preparing an oxygen electrode, characterized in that: The steps include: Conductive oxide electrode grains and a precursor solution of doped cerium oxide nanoparticles are mixed to obtain a mixed slurry, which is then dried to obtain a precursor-coated powder, followed by a first calcination to obtain a composite electrode powder, and then the composite electrode powder is mixed with battery glue to obtain an electrode slurry, which is then subjected to a second calcination to obtain the oxygen electrode.

9. Use of the oxygen electrode according to any one of claims 1 to 7 or the oxygen electrode prepared by the preparation method according to claim 8 in preparing a battery.

10. A solid oxide battery, characterized in that: It comprises the oxygen electrode according to any one of claims 1 to 7 or the oxygen electrode prepared by the preparation method according to claim 8, a fuel electrode and an electrolyte.

Citation Information

Patent Citations

  • Preparation method of composite cathode material for fuel cell

    CN111146456A

  • Symmetrical solid oxide fuel cell core-shell structure electrode material and preparation method and application thereof

    CN113991122A

  • Solid oxide electrolytic cell working electrode modified by binary alloy nano-particles as well as preparation method and application of solid oxide electrolytic cell working electrode

    CN114657579A

  • Low-temperature Solid Oxide Fuel Cell

    KR1020160136750A